Storage stability of the phenolic compounds, color and antioxidant activity of jambolan juice powder obtained by foam mat drying - Tavares, Iasnaia Maria de Carvalho; Sumere, Beatriz Rocchetti; Gómez-Alonso, Sergio; Gomes, Eleni; Hermosín-Gutiérrez, Isidro; Da-Silva, Roberto; Lago-Vanzela, Ellen Silva (Elsevier, 2020)
Jambolan (Syzigium cumini (L.) Skeels) stands out among the Brazilian fruits that are rich in bioactive compounds with potential for the production of dehydrated product. Therefore, jambolan juice powder was produced by foam mat drying method and stored for 150 days at three temperatures (4, 25, 35 °C). The effect of time, temperature and the interaction of these two factors on the qualitative and quantitative profile of phenolic compounds were determined after analysis of the powders by using HPLC-DAD-ESI-MSn. For the powders submitted to the different study condition, the concentration of flavonols did not differ from the control sample, and only a small reduction in the anthocyanins concentrations was seen (7-9%), only being significantly affected by storage time. Additionally, the molar profiles of these compounds were influenced more by time than storage temperature, however none of the compounds identified was totally degraded. The percentages of antioxidant activity oscillated during the storage time, however, without major losses after 150 days at all storage temperatures. The results showed that jambolan juice powder is very stable in terms of anthocyanins and flavonols concentrations at all three temperatures of the storage. This and the attractive color (purplish-red) make it a potential ingredient to enrich differentiated foods.
Keywords: Anthocyanins; Antioxidant activity; Bioactive compounds; Color parameters; cyanidin 3,5-glucoside (PubChem CID: 44256718); delphinidin 3,5-glucoside (PubChem CID: 10100906); ferric sulfate (PubChem CID: 24826); Flavonols; gallic acid (PubChem CID: 370); Jambolan; laricitrin 3-glucoside (PubChem CID: 44259475); malvidin 3,5-glucoside (PubChem CID: 44256978); myricetin 3-glucoside (PubChem CID: 44259426); myricetin 3-rhamnoside (PubChem CID: 5281673); petunidin 3,5-glucoside (PubChem CID: 10151874); Powder; Storage; syringetin 3-galactoside (PubChem CID: 44259488)